Materials Selection, Synthesis, and Dielectrical Properties of PVC Nanocomposites - Youssef Mobarak; M. Bassyouni; M. Almutawa (Advances in Materials Science and Engineering)
Materials selection process for electrical insulation application was carried out using Cambridge Engineering Selector (CES) program. Melt mixing technique was applied to prepare polyvinyl-chloride- (PVC-) nanofumed silica and nanomontmorillonite clay composites. Surface analysis and particles dispersibility were examined using scanning electron microscope. Dielectrical properties were assessed using Hipot tester. An experimental work for dielectric loss of the nanocomposite materials has been investigated in a frequency range of 10 Hz–50 kHz. The initial results using CES program showed that microparticles of silica and clay can improve electrical insulation properties and modulus of elasticity of PVC. Nano-montmorillonite clay composites were synthesized and characterized. Experimental analyses displayed that trapping properties of matrix are highly modified by the presence of nanofillers. The nanofumed silica and nanoclay particles were dispersed homogenously in PVC up to 10% wt/wt. Dielectric loss tangent constant of PVC-nanoclay composites was decreased successfully from 0.57 to 0.5 at 100 Hz using fillers loading from 1% to 10% wt/wt, respectively. Nano-fumed silica showed a significant influence on the electrical resistivity of PVC by enhancing it up to 1 × 1011 Ohm·m.